THE EFFECT OF PRICE, BRAND IMAGE AND PRODUCT QUALITY ON REALME SMARTPHONE PURCHASE DECISIONS AMONG THE PEOPLE OF EAST ACEH DISTRICT - Irvan Saputra; Khairina AR; Widyana Verawaty Siregar; T. Edyansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of price, brand image, and product quality on the purchasing decision of Realme smartphones among the people of East Aceh Regency. The population in this study were the people of East Aceh Regency who had purchased Realme smartphones. The research method used was a quantitative approach with a sample collection technique using purposive sampling. The data collected in this study were primary data, obtained through direct distribution of questionnaires using a non-probability sampling method, involving 100 respondents. For data analysis, multiple linear regression was used with the help of SPSS (Statistical Product and Service Solution) software version 26.0. At the stage of testing the research instrument, validity and reliability tests were applied. The findings of this study indicate that price and product quality have a positive and significant influence on the purchasing decision of Realme smartphones among the people of East Aceh Regency, while brand image shows a positive but insignificant influence on the purchasing decision of Realme smartphones among the people.